Computer models for estimating the performance of a given axial-flow gas turbine stage and for optimizing the efficiency - Kadıpaşaoğlu, A. Kamuran. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1984., 1984)
The present thesis involves the study of the aerodynamic performance of an axial-flow gas turbine stage. Existing studies have been reviewed and based on the most developed perfomance evaluation and efficiency optimization techniques, two computer programs have been developed. Given the geometry of a turbine stage, the inlet gas conditions and the rotational speed of the moving blades, the first program calculates the total-to-total isentropic efficiency of the stage and determi nes the gas conditions at the inlet and outlet of the blade rows. The second program, on the other hand, solves the inverse problem: For specified inlet gas conditions and blade rotational speed, the program determines the geometry of the tutbine stage for which the isentropic efficiency is an optimum. Both programs are applied to turbine stages operating at various inlet gas conditions and blade rotational speeds. The isentropic stage efficiency is observed to depend primarily on the overall pressure ratio, the initial mass flow parameter and the dimensionless speed of the stage. The results which are summarized in tabular and graphical forms are in conformity with those reported by the original authors. Finally, tecommendations are given for improving the precision of the perfonnance prediction method used.
Keywords: Gas-turbines -- Aerodynamics.; Gas-turbines.